Single-Dose Immunization With a Chimpanzee Adenovirus-Based Vaccine Induces Sustained and Protective Immunity Against SARS-CoV-2 Infection - Li, Mingxi; Guo, Jingao; Lu, Shuaiyao; Zhou, Runhong; Shi, Hongyang; Shi, Xuanling; Cheng, Lin; Liang, Qingtai; Liu, Hongqi; Wang, Pui; Wang, Nan; Wang, Yifeng; et al. (Frontiers in Immunology, 2021)
The development of a safe and effective vaccine against SARS-CoV-2, the causative agent of pandemic coronavirus disease-2019 (COVID-19), is a global priority. Here, we aim to develop novel SARS-CoV-2 vaccines based on a derivative of less commonly used rare adenovirus serotype AdC68 vector. Three vaccine candidates were constructed expressing either the full-length spike (AdC68-19S), or receptor-binding domain (RBD) with two different signal sequences (AdC68-19RBD and AdC68-19RBDs). Single-dose intramuscular immunization induced robust and sustained binding and neutralizing antibody responses in BALB/c mice up to 40 weeks after immunization, with AdC68-19S being superior to AdC68-19RBD and AdC68-19RBDs. Importantly, immunization with AdC68-19S induced protective immunity against high-dose challenge with live SARS-CoV-2 in a golden Syrian hamster model of SARS-CoV-2 infection. Vaccinated animals demonstrated dramatic decreases in viral RNA copies and infectious virus in the lungs, as well as reduced lung pathology compared to the control animals. Similar protective effects were also found in rhesus macaques. Taken together, these results confirm that AdC68-19S can induce protective immune responses in experimental animals, meriting further development toward a human vaccine against SARS-CoV-2.